Nonlinear response of cantilever beams due to large geometric deformations - Gonzalez-Cruz, Claudia Aide (Strojniški vestnik, 2016)
Many structural elements, such as gas turbine fans, wind turbine blades, springboards among others are designed as slender elements. Since their dynamic behaviour can be modeled as cantilever beams, it is important to understand their nonlinear behaviour due to large deformations. In this way, this work presents the experimental validation of a simplified model of a cantilever beam. The model is formulated considering large geometric deformations and assuming a Galerkin approach. The model is validated experimentally, and it is found that there is a characteristic frequency related to the nonlinear terms. The data is analysed using time-frequency maps produced with the continuous wavelet transform.
Keywords: fazni diagrami; harmonično popačenje; nelinearna dinamika; strukturno dušenje; velike geometrijske deformacije; zvezna valčna transformacija